(untitled) (Marketing Journal, 2026)
This study improved the methodology for environmentally innovative and sustainable development of the chemical industry. An integrated approach based on green chemistry principles, life-cycle assessment, and circular economy tools was developed. Environmental and economic indicators of chemical enterprises were analyzed. The results of digital management systems, resource efficiency improvements, and waste reduction measures were evaluated. The findings led to practical recommendations aimed at strengthening environmental safety, promoting innovation activities, and increasing the competitiveness and long-term sustainability of the chemical industry.